Serum 25(OH) Vitamin D Levels in Severely Obese Patients Evaluated Before Bariatric Surgery - YAVUZ, DİLEK; ELBASAN, ONUR (TURKIYE KLINIKLERI, 2020)
Objective: Obesity is a risk factor for vitamin D deficiency, which is reported to be detected differently in each population. This study aimed to evaluate the 25(OH) vitamin D (25(OH)D) levels, intact parathormone (iPTH) levels, and their relationship with body mass index (BMI) in obese patients, screened prior to bariatric surgery. Material and Methods: This retrospective study comprised of 1.082 obese patients (41 +/- 10 years, female/male: 823/259) who were candidates for bariatric surgery. BMI, waist circumference (WC), serum 25(OH)D, iPTH, calcium, phosphorus values of these patients were recorded from patient files. Results: BMI, WC, iPTH, and 25(OH)D levels were 48 +/- 8.9 kg/m(2), 128 +/- 11.9 cm, 64 +/- 36 pg/mL, and 15 +/- 18 ng/mL, respectively. Mean 25(OH)D level of 79.1% of the patients belonged to the deficiency range. Very low 25(OH) vitamin D levels (<10 ng/mL) were witnessed among 40.9% (443/1.082) of the study group. Female obese subjects possessed significantly lower serum 25(OH)D levels as compared to male obese patients. Significant negative correlations were perceived between 25(OH)D levels and iPTH (r=-0.34, p<0.0001), BMI (r=-0.20, p<0.0001), and waist circumferences (r=-0.14, p=0.002) in the whole group. Multivariate analysis indicated that BMI to be an independent risk factor for vitamin D deficiency. Conclusion: A high rate of vitamin D deficiency was documented in our morbidly obese patients who were candidates for bariatric surgery. BMI is a determinant of 25(OH)D levels. It is essential to screen for vitamin D deficiency and possible osteomalacia among the candidates for bariatric surgery of obese patients and should be treated appropriately before bariatric surgery.
Keywords: Obesity; vitamin D; bariatric surgery; vitamin D deficiency; D DEFICIENCY; BREAST-CANCER; PREVALENCE; 25-HYDROXYVITAMIN-D; RISK; PREVENTION; FREQUENCY; HEALTH